Young Youth Stay Away from Drugs and the Dangers of Underage Marriage - Silfa Hafizah Pulungan (PT Inovasi Pratama Internasional, 2023)
Catin who married in Sosopan Village, Kec. Kab. Padang Lawas has increased every year. failure For take continuing education because parents' economic gap is one of the causes of adolescents making the decision to marry even though they are not ready or mature psychologically, mentally and emotionally. Through this socialization activity